(untitled) (Dissertare, 2022)
Teaching and learning today are complex processes that demand the promotion of thought in its various modes of operation; this implies inserting the subjects of the educational act in the commitment to cognitively dispose themselves to display higher-order skills,mental skills and operations that allow them to act significantly on the knowledge and reality of which they are part.This procedure poses the challenge of guiding educational praxis towards the use of criticality, analysis and reflexivity. Cognitive activities that, due to their implications, favor an effective approach to the knowledge and information frameworks required at all educational levels.In this sense, this essay is the result of a documentary research, in which a characterization of the ways in which thought operates is proposed, which is assumed to be a process that favors the critical, reflective, analytical processing of accumulated knowledge,as an input from which to dimension the possibilities to create possible worlds, face the challenges of each scientific community and proceed in an intelligent, flexible and autonomous way in the face of the challenges of a world saturated with complex and diverse information. It is concluded that the teaching and learning processes require the operational promotion of the modes of thought, with the purpose of favoring the formation of reflective subjects, capable of looking at reality from different angles, establishing new connections and making appropriate decisions.